El Ave María en idioma mochica - Salas García, José Antonio (Mercurio Peruano, 2020)
The aim of this article is to translate the Ave Maria prayer from Mochica language into Spanish. We will compare both versions of this prayer, which belong to Luis Jerónimo de Oré (1607) and Fernando de la Carrera (1644), and then we will interpret some questions and answers which Fernando de la Carrera offers.